Business Sustainability of Food Industry on Selected Micro-Enterprise in Brgy Sta. Monica Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the business sustainability of the food industry inselected micro-enterprises in Brgy Sta. Monica Quezon City in terms of responsibility,accountability, compliance, reliability, responsiveness, and assurance; the significantrelationship between sustainability and performance in terms of aforecited variables; problemencountered of selected micro-enterprise and recommendation to address the followingtechniques to develop more or maintain the business sustainability.The result of this study reveals that the business sustainability of the food industry is evaluatedas Always in terms of responsibility and accountability, and the Performance of sustainabilityis evaluated as Excellent performance in terms of compliance, reliability, responsiveness, andassurance; the problem encountered of selected micro-enterprise is the inflation rate, lack ofcapital or cash flow, lack of proper marketing and too many competitors the techniques todevelop more or maintain the business sustainability is to develop a unique marketing strategyand stay ahead in terms of quality, price and customer service.This study recommends a developing strategy to compete with competitors, develop a uniquemarketing strategy, and stay ahead in terms of quality, price, and customer service.
Keywords: Business